THE IMPLEMENTATION OF COMPANY’S CSR PROGRAM IN EMPOWERING THE ECONOMY OF RURAL COMMUNITIES DURING THE COVID-19 PANDEMIC - Sandra Dewi (JCH (Jurnal Cendekia Hukum), 2021)
This research aims to explain the implementation of the company's CSR program in empowering the economy of rural communities during the Covid-19 pandemic based on Riau Provincial Regulation Number 6 of 2012. The method of the research is socio-legal research. The results of the research explain that the Covid-19 Pandemic has the impact toward the sustainibility local economy of Riau Province, including the people of Palas Village. In addition for expecting social grant from the government, one great opportunity for inhabitants of Palas Village for the enhancement of local economy condition must based on the application on the CSR programs of companies operating system in Pelalawan Regency. Companies that carry out their business activities in the field of natural resources and / or fields related to natural resources must require to carry out CSR. Based on Article 32 of Riau Provincial Regulation Number 6 of 2012, it is stated that companies that do not implement CSR will be worned of administrative sanctions in the form of written warnings and restrictions on business activities, freezing of business activities, and revocation of business activities.